Effect of temperature in titanium chemical mechanical planarization. (22nd June 2015) - Mu, Yan; Jiao, Yubo; Sampurno, Yasa; Zhuang, Yun; Theng, Siannie; Philipossian, Ara
Abstract: The effect of temperature on the tribological and kinetic attributes of Ti chemical mechanical planarization (CMP) was investigated. Results indicated that processes at platen temperatures of 25 and 50 °C behaved similarly in terms of their tribological mechanism. At both temperatures, average coefficient of friction (COF) ranged from 0.19 to 0.41, indicating that boundary lubrication was the dominant tribological mechanism. Results also showed that average COF decreased with increasing platen temperature likely due to softening of pad asperities and lower slurry viscosity at the higher temperature. Due to exponentially accelerated chemical effects, Ti removal rate was higher when platen temperature was set at 50 °C. A two-step modified Langmuir–Hinshelwood model was used to simulate Ti removal rate and the chemical and mechanical rate constants under different polishing conditions. Simulated values of removal rate agreed well with experimental data. Simulated chemical rate to mechanical rate constant ratios suggested that the removal mechanism shifted from a more chemically-controlled to a more mechanically-controlled process as platen temperature was raised.